Evidence for a hijacked brain reward system but no desensitized threat system in quitting‐motivated smokers: An fMRI study. (18th September 2021) - Kunas, Stefanie L.; Stuke, Heiner; Heinz, Andreas; Ströhle, Andreas; Bermpohl, Felix
Abstract: Background and aims: Several aspects of how quitting‐motivated tobacco use disorder (TUD) subjects and never‐smokers differ in terms of reward and threat processing remain unresolved. We aimed to examine aberrant reward and threat processes in TUD and the association with smoking characteristics. Design: A between‐ and within‐subjects functional magnetic resonance imaging (fMRI) experiment with a 2 (groups) × 4 (stimulus type) factorial design. The experimental paradigm had four conditions: pictures of (1) cigarettes served as drug‐related‐positive cues, (2) food as alternative reward cues, (3) long‐term consequences of smoking as drug‐related‐negative cues and (4) neutral pictures as control. Setting/participants: Adult participants ( n  = 38 TUD subjects and n  = 42 never‐smokers) were recruited in Berlin, Germany. Measurements: As contrasts of primary interest, the interactions of group × stimulus‐type were assessed. Significance threshold correction for multiple testing was carried out with the family‐wise error method. Correlation analyses were used to test the association with smoking characteristics. Findings: The 2 × 2 interaction of smoking status and stimulus type revealed activations in the brain reward system to drug‐related‐positive cues in TUD subjects (between‐subjects effect: P ‐values ≤ 0.036). As a response to drug‐related‐negative cues, TUD subjects showed no reduced activation of the aversive brain network. Within the TUD group, a significant negative association was found between response of the aversive brain system to drug‐related‐negative cues (within‐subjects effect: P ‐values ≤ 0.021) and the number of cigarettes smoked per day (right insula r  = −0.386, P  = 0.024; left insula r  = −0.351, P  = 0.042; right ACC r  = −0.359, P  = 0.037). Conclusions: Moderate smokers with tobacco use disorder appear to have altered brain reward processing of drug‐related‐positive (but not negative) cues compared with never smokers.